Guideline for Tranmission of Hiit Sibsong Tradition (Twelvemonths Tradition) to Empowerment Community - คำผา, กาญจนา; แนวแห่งธรรม, รัชฎาพร เกตานนท์ (Ratchaphruek Journal, 2018)
ABSTRACT The research aims tostudy1)relation of community context, history and tradition of Sammeun village, Feung, Vientiane, Lao PDR and Baan Na Vieng, SaiMool, Yasothorn, Thailand, 2) roles and values of Hiit Sibsong tradition in empowerment community, and 3) guidelines for transmission of Hiit Sibsong tradition in Baan Na Vieng. Thisis a qualitative research, which the in-depth interview and the focus group were used, also the descriptive analysis was used to the discussion and presentation.The research finds that 1) history and socio-cultural aspects of Sammeun village have evidences to assume that Baan Na Vieng has its ancestry back to Sammeun village where has the divination and antiques of small Buddha images. Moreover, Sammeun villagers are Lao Phuan people who have continuously held on traditions for life, 2)Hiit Sibsong tradition play many roles on empowerment community:to maintain Buddhism, to enhance family and kinship stability, and to enhance relation system within and between community.Socially, Hiit Sibsong encourages local to have faith in local culture, empowerment community’s budget management and give community a sense of local pride. It is also valuable for community development in many aspects:economics, education, government, communication, technology as well as public health, and 3) the guidelines for the transmission Hiit Sibsong tradition are (a) adapt monthly practice of Hiit Sibsong to suit social context, (b)multiply modern and various public relation channels and (c) promote the youth participation in the Hiit Sibsong tradition.